Thursday

April 17, 2014

April 17, 2014

Posted by **John** on Saturday, July 16, 2011 at 10:09pm.

- math -
**Reiny**, Saturday, July 16, 2011 at 10:16pmg(-1+h) = (-1+h)^2 - 7(-1+h) + 5

= 1 - 2h + h^2 + 7 - 7h + 5

= h^2 - 9h + 13

g(-1) = 1 + 7 + 5 = 13

( g(-1+h) - g(-1) )/h = (h^2 - 9h + 13 - 13)/h

= h - 9

**Related Questions**

algebra1 - Evaluate each funtion for the given input values: for f(x)=4x-3,find ...

math - what is the translation that maps the funtion f(x)= x squared - 1 onto ...

math - Let f:A->B, where A and B are nonempty, and let T1 and T2 be subsets ...

Calc - Evaluate the following indefinite integral integral of the funtion (x^3...

Math - How would you tell if an equation is a funtion or not. I know that it has...

Algebra - 7t^4 • 7t^4 A.49t8 B.14t4 C.49t16 D.14t8 Is this 49t^8...A..?

math - can someone please help me with this question. Given the funtion f(x)= 3x...

math - after ploting graph for h = 1.1 + 7t - 5t^2 for interval t = 0 to t = 2. ...

algebra - Help me find the axis of symmetry of the given funtion. Y=x2-2x+4

Calculus - How do you find the integral (antideriv) of 12 / (7t + 6) ???????? I ...